Developing English Teaching Materials Based on Local Wisdom for the Tenth Grade Students at SMA Negeri 1 Alasa - Hulu, Niguents Faldes; Zebua, Elwin P.; Harefa, Afore T.; Maru’ao, Nursayani (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The Merdeka Curriculum assumed the integration of local wisdom into teaching materials because it contained noble values that could develop knowledge to shape students' character and increase their motivation to learn. English teachers at SMA Negeri 1 Alasa still used general teaching materials and had not specifically incorporated the local wisdom of the Nias tribe. One of the Nias local wisdoms that could be integrated into English learning was folktales in the form of legends for Narrative Text material. Thus, this research aimed to produce visual book teaching materials based on local wisdom that were suitable and practical to use. This research used the Research and Development method, employing the 4D development model. The results showed that the visual book teaching materials developed by the researcher were very suitable and practical to use, as evidenced by the results of the validation and practicality questionnaires. Validation results by language experts, with an average score of 4, were in the very feasible category with a percentage of 100%. Validation results by media experts, with an average score of 3.8, were in the very feasible category with a percentage of 95%. Validation results by material experts, with an average score of 3.86, were in the very feasible category with a percentage of 96.66%. The results of the practicality test by teachers and students were in the very practical category, with the highest percentage being 100% and the lowest percentage being 88.66%. Based on these results, it was concluded that the development of English teaching materials based on local wisdom for the tenth-grade students at SMA Negeri 1 Alasa was feasible and practical for use in the learning process. It was recommended that teachers develop teaching materials based on local wisdom in the region for other learning content.